K-Means on GPU: A Review (International Journal of Engineering and Computer Science, 2014)
K-Means is the most popular clustering algorithm in data mining. The size of various data sets has increased tremendously day by day. Due to recent development in the shared memory inexpensive architecture like Graphics Processing Units (GPU). The general – purpose applications are implemented on GPU using Compute Unified Device Architecture (CUDA).  Cost effectiveness of the GPU and several features of CUDA like thread Divergence and coalescing memory access. Shared memory architecture is much more efficient than distributed memory architecture.